2016
DOI: 10.1002/cssc.201600999
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Water Vapor on the Stability and Processing of Hybrid Perovskite Solar Cells Made from Non‐Stoichiometric Precursor Mixtures

Abstract: We investigated the influence of moisture on CH3NH3PbI3 perovskite films and solar cells derived from non-stoichiometric precursor mixtures. We followed both the structural changes under controlled air humidity via in-situ X-ray diffraction, and the electronic behavior of devices prepared from these films. A small PbI2 excess in the films improved the stability of the perovskite compared to stoichiometric samples. We assign this to excess PbI2 layers at the perovskite grain boundaries or to the termination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(109 citation statements)
references
References 47 publications
4
102
2
Order By: Relevance
“…Under these harsh conditions, our pristine layered MASI films partly recrystallized to the zero-dimensional phase after 10 h. In the course of further tracing the phase transition, we found a complete transformation to the dimer phase after 50 h. Further continuous moisture exposure for one week results in an oxidized antimony-containing phase as confirmed via energy dispersive X-ray analysis, shown in the SI. The observed instability towards moisture of the MASI compound is much less pronounced than that of MAPbI 3 [13]. Studies with much thinner 2D-MASI films obtained from EtOH show that the sensitivity towards moisture becomes more evident, indicating a strong influence of morphology on stability (see SI).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Under these harsh conditions, our pristine layered MASI films partly recrystallized to the zero-dimensional phase after 10 h. In the course of further tracing the phase transition, we found a complete transformation to the dimer phase after 50 h. Further continuous moisture exposure for one week results in an oxidized antimony-containing phase as confirmed via energy dispersive X-ray analysis, shown in the SI. The observed instability towards moisture of the MASI compound is much less pronounced than that of MAPbI 3 [13]. Studies with much thinner 2D-MASI films obtained from EtOH show that the sensitivity towards moisture becomes more evident, indicating a strong influence of morphology on stability (see SI).…”
Section: Resultsmentioning
confidence: 97%
“…These exceptional material properties originate from a combination of high crystal symmetry, the chemistry of the Pb 6s 2 lone-pair states and the ionic nature of the structure with large atomic sizes [9]. However, the toxicity of lead together with the instability of this and related perovskite compounds towards moisture and high temperature limit the commercialization of lead-based perovskite solar cells [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…[45,223] Petrus et al have recently investigated the influence of moisture on MAPbI 3 films and solar cells derived from nonstoichiometric precursor mixtures. [101] They followed both the structural changes under controlled air humidity (Figure 13) through in situ X-ray diffraction, and the electronic behavior of devices prepared from these films. The results showed that a small excess of PbI 2 in the films improved the stability of the perovskite compared to stoichiometric samples.…”
Section: Moisturementioning
confidence: 99%
“…The reason for that is still unclear but might be associated with the uncompleted conversion of the precursors into perovskite using the two‐step methodology. In fact, Petrus et al prepared CH 3 NH 3 PbI 3 films in an analogous way and the authors used the sequential deposition method to study the stability of these samples. In both cases, the incomplete conversion of PbI 2 into the perovskite phase led to a residual PbI 2 interlayer between TiO 2 and perovskite, which was reported to accelerate the film degradation.…”
Section: Resultsmentioning
confidence: 99%
“…As demonstrated by Petrus et. al., the preferred orientation of the 2D structures is fundamental for charge collection; thus, more controlled deposition is required using the protocol described herein …”
Section: Resultsmentioning
confidence: 99%